Theater Elements of Mandiek Anak In Salareh AIA - Risa Erdila; Nur Sahid; Surya Farid Sathotho (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
This study aims to analyze the theatrical elements found in mandiekanak. Mandiekanak is a ritual that is part of BaralekGadang and only found in the Salareh Aia region. This research uses Schechner's performance studies approach to analyze research subjects. According to Carlson, the concept of cultural performance is used to look deeper at the events of mandiekanak. It also uses Dramaturgy theory to see the theatrical element while qualitative research methods collect data in purposive sampling. The collected data is then analyzed descriptively using ethnographic methods. The analysis results showed that the mandiekanak has the purpose of maintaining the family of the bride's father or bako, as for the theatrical elements in the form of scripts, performers, audiences, and venues. Manuscripts are rules that ensure the survival of a mandiekanak. The player refers to all people who are involved in it. The mandiekanak audience is participatory, while the place refers to the area where the mandiekanak exists